KARAKTERISTIK ASAM AMINO DAN ASAM LEMAK BEKASAM KERANG BULU (Anadara antiquate) DI DESA BENAN KABUPATEN LINGGA - Putra, M. Desra Hari; Putri, R. Marwita Sari; Oktavia, Yulia; Ilhamdy , Aidil Fadli (Marinade, 2020)
Formation of feather shells (Anadara antiquata) which has been carried out the characteristics of amino acids and fatty acids obtained the highest amino acid yield is Arginine 10293.28, and the lowest histidine is 136.91. The highest saturated fatty acid is palmitic which is 1.20 and the lowest lauric acid is 0.09, the highest monounsaturated fatty acid is glutamic acid 17257.96, and the lowest is alanine 312.56, the highest polyunsaturated fatty acid is linoleic 0.58, linolenic acid 0.58, and the lowest arachidonic acid 0.29.